2020
DOI: 10.3389/fnmol.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Clinical Presentations Due to Variations in THOC2 mRNA Nuclear Export Factor

Abstract: Multiple TREX mRNA export complex subunits (e.g., THOC1, THOC2, THOC5, THOC6, THOC7) have now been implicated in neurodevelopmental disorders (NDDs), neurodegeneration and cancer. We previously implicated missense and splicingdefective THOC2 variants in NDDs and a broad range of other clinical features. Here we report 10 individuals from nine families with rare missense THOC2 variants including the first case of a recurrent variant (p.Arg77Cys), and an additional individual with an intragenic THOC2 microdeleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“… ( a ) Recombinant human THO (top), THO ∆THOC6 (middle), THOC1/2/3 (bottom) complex migration in sucrose density gradients (SDS-PAGE stained with Coomassie blue) indicates an oligomeric state consistent with tetramer, dimer, and monomer architectures, respectively. ( b ) Location of human disease-associated mutations in THOC2 ( Kumar et al, 2020 ; Kumar et al, 2018 ; Kumar et al, 2015 ) and THOC6 ( FORGE Canada Consortium et al, 2013 ; Casey et al, 2016 ; Anazi et al, 2016 ; Care4Rare Canada Consortium et al, 2017 ; Mattioli et al, 2019 ). Several THOC6 mutations were shown to affect its stability and lead to the loss of interaction with THO subunits ( Mattioli et al, 2019 ), suggesting that stabilization of the THO tetramer is needed for its full activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… ( a ) Recombinant human THO (top), THO ∆THOC6 (middle), THOC1/2/3 (bottom) complex migration in sucrose density gradients (SDS-PAGE stained with Coomassie blue) indicates an oligomeric state consistent with tetramer, dimer, and monomer architectures, respectively. ( b ) Location of human disease-associated mutations in THOC2 ( Kumar et al, 2020 ; Kumar et al, 2018 ; Kumar et al, 2015 ) and THOC6 ( FORGE Canada Consortium et al, 2013 ; Casey et al, 2016 ; Anazi et al, 2016 ; Care4Rare Canada Consortium et al, 2017 ; Mattioli et al, 2019 ). Several THOC6 mutations were shown to affect its stability and lead to the loss of interaction with THO subunits ( Mattioli et al, 2019 ), suggesting that stabilization of the THO tetramer is needed for its full activity.…”
Section: Resultsmentioning
confidence: 99%
“…b. Location of human disease-associated mutations in THOC2 (Kumar et al, 2020(Kumar et al, , 2018(Kumar et al, , 2015) and THOC6 (Beaulieu et al, 2013;Casey et al, 2016;Anazi et al, 2016;Amos et al, 2017;Mattioli et al, 2019). Several THOC6 mutations were shown to affect its stability and lead to the loss of interaction with THO subunits (Mattioli et al, 2019), suggesting that stabilization of the THO tetramer is needed for its full activity.…”
Section: Model Of Mrna Export Licensingmentioning
confidence: 99%
“…NOVA2 as an AS factor [ 87 ] has been confirmed that it may participate in the occurrence of breast cancer by promoting epithelial-mesenchymal transition [ 88 ]. In addition, studies have shown that THOC6 is related to cancer [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…A search in PubMed using the keyword “ THOC2 ” led to a list of only 17 papers. A total of three seminal papers by Kumar et al have a clinical and genetic characterization of families with THOC2 gene mutations [ 7 , 8 , 9 ]. The findings in these papers have been summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 99%